POTENSI JENIS DAN STRUKTUR TUMBUHAN SUKU PALA-PALAAN (Myristicaceae) DI TAMAN WISATA ALAM GUNUNG MEJA MANOKWARI - Matheus Beljai (AGRICOLA, 2016)
Gunung Meja Natural Tourism Park (GMNTP) as one of a nature conservation area in Manokwari has potency of flora that not been much revealed, for example is Myristicaceae. The study aims to determine the potential of the type and structure of flora Pala-Palaan (Myristicaceae) in GMNTP. The method used is descriptive method with survey techniques. Observations flora of Myristicaceae be done of the seedlings, saplings, poles, and tree. The observation of the seedlings, saplings and poles, using line plot sampling methods, while at the level of the tree using a continuous strip sampling methods. The data collected is the number of species, the number of individuals of each species and diameter. Analysis of data is using formulas the forest vegetation analysis of Dombois and Ellenberg (1974) which includes: density, relative density, frequency, relative frequency, dominance and relative dominance. From the research, it was discovered five species of Myristicaceae family, namely: Myristica simisifera R. Br., Myristica holrungii Warb., Horsfieldia sylvestris Warb., Myristica sulcata Warb., and Knema sp. The results of quantitative analysis showed that the type of dominant seedlings and saplings is Myristica sulcata Warb. (39.716% and 32.434%), whereas at the level of the pole is Horsfieldia sylvestris Warb. (61.420%). For the tree, the dominant species is Myristica sulcata Warb. (44.719%). The above conditions illustrates that Myristica sulcata Warb. as one species of  family Myristicaceae that relatively stable in terms of density and presence on GMNTP. It can be seen from the dominance of this species of the three levels, namely seedlings, saplings and trees.